A HISTORICAL APPRAISAL OF LEADERSHIP CHALLENGES IN NIGERIA, 1914-1979 (LAPAI JOURNAL OF NIGERIA HISTORY, 2024)
The focus and overall purpose of this paper is to attempt a historical appraisal of leadership challenges in Nigeria from 1914 which marked the amalgamation of the Northern Protectorate with the Southern Protectorate which gave birth to Nigeria as a nation, while the terminating period of the study is 1979, which marked the end of the military regime and beginning of the Second Republic. However, using historical methodology and dependency theory the paper argued that the major root of problems of leadership in Nigeria are associated with colonial policies of divides and rule, ethnicity and regionalism imposed through indirect rule system of administration. Also, the paper has argued that the political instabilities of the First Republic such as the 1962/1963 census controversies, 1964 and 1965 federal and regional election violence, political crisis in the Western Region as well as intense agitations for the creation of more regions, military intervention in Nigerian politics and of course foreign interventionism were the key factors that played a significant role in the problems and challenges of leadership in Nigeria. Finally, the paper provides some recommendations towards the remedy of leadership challenges in Nigeria.